Round robin tests of secondary raw materials: A systematic review of performance parameters - Korf Nathalie; Mählitz Paul Martin; Rotter Vera Susanne (Reviews in Analytical Chemistry, 2022)
An improved management of secondary raw materials (SRM) is a crucial contribution for a circular economy and necessitates knowledge about the composition of wastes and SRM. However, this information is scarce and has to be determined with chemical analysis (CA). CA of SRM faces challenges, which can be approached by using round robin tests (RRT) to identify deviations from the “true value” of an element/molecule content. An RRT is a testing approach, which involves multiple labs to analyze one or more samples and evaluates the lab results with regard to the goal of the RRT. This article presents a systematic literature review and investigates which purposes and which performance parameters (PP) are commonly applied in RRT of SRM. The examined literature shows that the two main purposes applied are assessment of method performance and assessment of lab performance. PP can be categorized into trueness performance parameters (TPP; assessing the deviation of a value from a reference value) and precision performance parameters (PPP; describing the variability of a data set). The main TPP identified are z score and relative deviation, the main PPP identified are standard deviation and relative standard deviation. These results offer the conclusions that RRT can be used as a bespoke method to deal with analytical effects and that the selection of PP for an RRT could be based on simplicity.